Mengungkap Seluk Beluk Pendidikan dan Pelatihan dari Optik Administrasi di Lingkungan Birokrasi Pemerintahan - Suhady, Idup (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
Training and development has an important role in constructing and mantaining a dedicated and professional public servant. Based on organizational and management function, training and development for public servant has two main functions as a managing system of public servant career and also to support national education system. This article tries to explore training and development system in government scope, especially from administration perspective that covers institutional aspect, human resource and training management as one comprehensive package